Building Blocks Of Industry - Industrial Minerals In 1968 - Asbestos - Paul A. Filteau (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1969)
Asbestos ranks among the leading minerals produced in Canada. It is also mined in Russia, Rhodesia, South Africa, Cyprus, Italy, the U.S.A., Japan, China and several other countries. The most abundant variety, chrysotile, and also the most valuable form of asbestos produced, makes up 90% of the world's supply. In Canada, chrysotile is found in the provinces of British Columbia, Ontario, Newfoundland as well as in Quebec, the latter accounting for almost 90% of all the fibre produced in this country. A number of developments emerging this year could make 1968 a record production and export year for Canada's asbestos mining industry. Asbestos fibre consumption in increasing in the U.S., Canada, up 10% to date this year, Japan and in Latin America. Demand in Western Europe is again on the upswing, following a cut-back last year. As a result, shipments from Canadian mines for the first eight months of this year reached some 916,968 tons versus 873,402 in 1967, an increase of 43,566 tons or 5%. Indications are that Canadian asbestos production will for the first time ever top 1.5 million tons in 1968.